2002
DOI: 10.1111/j.1572-0241.2002.07103.x
|View full text |Cite
|
Sign up to set email alerts
|

Balsalazide Is Superior to Mesalamine in the Time to Improvement of Signs and Symptoms of Acute Mild-to-Moderate Ulcerative Colitis

Abstract: Balsalazide is an effective and safe treatment for mild-to-moderate ulcerative colitis. Improvement of symptoms occurs considerably earlier with balsalazide than with mesalamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…57.32), as detailed earlier in this chapter. Head-to-head blinded randomized studies with equimolar doses of azo-bond release balsalazide and pH-release mesalamine have shown superior remission rates, earlier time to complete absence of symptoms, as well as other outcomes favoring balsalazide in some, but not all, studies [670][671][672]. Whether this benefit extends to other azo-bond release agents has not been firmly established [381,673].…”
Section: Mild Diseasementioning
confidence: 99%
“…57.32), as detailed earlier in this chapter. Head-to-head blinded randomized studies with equimolar doses of azo-bond release balsalazide and pH-release mesalamine have shown superior remission rates, earlier time to complete absence of symptoms, as well as other outcomes favoring balsalazide in some, but not all, studies [670][671][672]. Whether this benefit extends to other azo-bond release agents has not been firmly established [381,673].…”
Section: Mild Diseasementioning
confidence: 99%
“…The quality of the remaining studies was assessed by use of the Jadad score (Table 1). Of the six studies, five achieved Jadad a score of 3 or more [16][17][18][19][20] and other achieved a Jadad score of 2 [15]. Regarding the Cochran Q test for heterogeneity, it was found that all studies were homogenous and could be combined and meta-analyzed by fixed effects.…”
Section: Resultsmentioning
confidence: 99%
“…Two reports were considered ineligible, and thus, six trials remained ( Fig. 1) [15][16][17][18][19][20]. The quality of the remaining studies was assessed by use of the Jadad score (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, newer ASA derivates, such as balsalazide, were shown to be effective and safe for the treatment of mild-tomoderate colitis. 37 Patients who do not respond adequately to the standard dose should be treated at a higher dose. Should monotherapy with 5-ASA not prove satisfactory, combination treatment with local corticosteroids is recommended.…”
Section: Endoscopymentioning
confidence: 99%